(untitled) (Revista Justiça do Direito, 2024)
This article aims to analyze the existing relationships among gender, nature and power in the consumer society. Thus, it intends to answer to the problem: can the Good Way of Living be considered an ecofeminist practice in the consumer society, where the gender inequality and the exploitation of nature go side by side? To answer the question, the chosen method was the analytical, once that meets the need for analysis of legal-bibliographic references. By way of conclusion, it can be stated that the market power, in the consumer society, has remained oppressive in relation to the domination of women and the exploitation of nature. However, new proposals, opposed to the guidelines established by capital, find in Latin American hetero-patriarchal society a productive locus to question the maintenance of gender inequalities and the ecological destruction. The Good Way of Living, pillar of Ecuador’s Constitution, presents itself as an audacious idea where ecology and feminism begin to meet the projection of a better world.